Effective Biopesticides and Biostimulants to Reduce Aflatoxins in Maize Fields - Lagogianni, Christina S.; Tsitsigiannis, Dimitrios I. (Frontiers in Microbiology, 2019)
Τhe presence of ear rots in maize caused by Aspergillus flavus that are also associated with the production of aflatoxins has evolved into an increasing problem over the last few years. Since no commercial biological control products are still available to control A. flavus in maize in Europe, this study targets to the evaluation of six biopesticides/biostimulants (Botector®, Mycostop®, Serenade Max®, Trianum®, Vacciplant® and Zeolite) for the control of A. flavus and the derived aflatoxins in in vitro and maize field bioassays. Mycostop®, Serenade Max®, Vacciplant® and Zeolite reduced significantly A. flavus conidia production by 38,8% to 63,1% and most of them were able to reduce aflatoxin B1 (AFB1) production in laboratory studies. Mycostop®, Trianum® and Botector® were effective in reducing AFB1, in vitro. In the field, Mycostop® and Botector® treatments resulted in significant reduction of the disease severity (16,5% and 21,9% respectively) and decreased significantly AFB1 content in maize kernels by 43,05% and 43,09% respectively. For the first time, these results demonstrated the potential of commercial non-chemical products to suppress disease symptoms and aflatoxin content caused by A. flavus in maize under laboratory and field conditions.